CHESS: A systematic testing tool for concurrent software - Musuvathi, Madan; Qadeer, Shaz; Ball, Thomas (2007)
Concurrency is used pervasively in the development of large systems programs. However, concurrent programming is difficult because of the possibility of unexpected interference among concurrently executing tasks. Such interference often results in "Heisenbugs" that appear rarely and are extremely difficult to reproduce and debug. Stress testing, in which the system is run under heavy load for a long time, is the method commonly employed to flush out such concurrency bugs. This form of testing provides inadequate coverage and has unpredictable results. This paper proposes an alternative called concurrency scenario testing which relies on systematic and exhaustive testing We have implemented a tool called CHESS for performing concurrency scenario testing of systems programs. CHESS uses model checking techniques to systematically generate all interleaving of a given scenario. CHESS scales to large concurrent programs and has found numerous previously unknown bugs in systems that had been stress tested for many months prior to being tested by CHESS. For each bug, CHESS is able to consistently reproduce an erroneous execution manifesting the bug, thereby making it significantly easier to debug the problem. CHESS has been integrated into the test frameworks of many code bases inside Microsoft and is being used by testers on a daily basis.